Molecular detection of Leishmania infantum DNA according to clinical stages of leishmaniasis in dog - Murilo Antônio Fernandes; João Augusto Franco Leonel; Jéssica Anzolin Isaac; Julia Cristina Benassi; Diogo Tiago Silva; Julio Cesar Pereira Spada; Nuno Wolfgang Balbini Pereira; Helena Lage Ferreira; Lara Borges Keid; Rodrigo Martins Soares; Trícia Maria Ferreira de Sousa Oliveira (Revista Brasileira de Parasitologia Veterinária)
Abstract The aim of this study was to compare molecular tests used to diagnose Leishmania spp. in dogs with different stages of infection. Blood and conjunctival swab (CS) samples from dogs classified in four clinical stages were subjected to different PCR protocols (13A/13B, MC1/MC2, LITSR/L5.8S and LEISH-1/LEISH-2 primers). To the study, 22.3% (48/215) of dogs were classified as without clinical signs, 67.5% (145/215) stage I (mild disease), 7.0% (15/215) stage II (moderate disease) and 3.2% (7/215) stage III (severe disease). The results showed that in blood samples, 13A/13B detected a significant higher number of positive dogs in stage I (25/145) and in total (42/215) (p≤0.05). However, when CS samples were tested, no difference was observed (p>0.05). On the other hand, in blood samples, MC1/MC2 detected significantly fewer positive dogs classified as without clinical signs (0/48), in stage I (0/145) and in total (1/215) (p≤0.05). Likewise, in CS samples, this primers showed also lower detection (1/215) (p≤0.05). So than, we can conclude that PCR on blood samples with 13A/13B primers has greater capacity to detect positive dogs, mainly at the initial of clinical disease than do other primers and MC1/MC2 are not a good choice to detect Leishmania infantum infection in dogs.